Seismic assessment of a vernacular rammed earth building - Librici, Camilla (2017)
Rammed earth constructions represent a valuable cultural heritage of vernacular architecture, whose significance has acquired even more importance in the last years with the renovated interest for this sustainable building technique. The aim of this work is to develop a FEM model typologically representative of a Portuguese vernacular rammed earth construction in order to characterize numerically its seismic performance and raise awareness about the level of improvement introduced by two compatible strengthening techniques: textile reinforced mortar (TRM) and a ring beam applied at the top of the walls.